2021
DOI: 10.2478/aoas-2020-0118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rye Grain Derived from Different Cultivars or Maize Grain Use in the Diet on Ruminal Fermentation Parameters and Nutrient Digestibility in Sheep

Abstract: Six wether sheep with ruminal and duodenal cannulas were used in a replicated 3 × 3 Latin square to determine the effect of rye grain (from an open-pollinated or a hybrid cultivar) and maize grain from hybrid cultivar inclusion in the diet on ruminal fermentation parameters and nutrient digestion in different gastrointestinal tract compartments. The experimental diets consisted of meadow hay (800 g/day) and a concentrate mixture (300 g/day) that contained rye grain from an open-pollinated cultivar (OPRG), rye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Consequently, it is not surprising that RYE had reduced final pH compared to the two corn treatments and that the final pH for HMC was less compared to DRC given the increased IVDMD differences observed in the current experiment. These pH differences agree with those previously observed comparing rye to dry corn [8] and between HMC and DRC [10].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consequently, it is not surprising that RYE had reduced final pH compared to the two corn treatments and that the final pH for HMC was less compared to DRC given the increased IVDMD differences observed in the current experiment. These pH differences agree with those previously observed comparing rye to dry corn [8] and between HMC and DRC [10].…”
Section: Resultssupporting
confidence: 92%
“…The increased IVDMD for rye grain agrees with other observations where rye grain was more rapidly available in the rumen compared to barley [6] or corn [7]. Differences in degradability between feed grains are related to the molecular structure of the protein matrix surrounding starch granules [6] [7] [8]. Another potential explanation for the increased IVDMD for rye grain is greater concentrations of alkylresorcinols in rye compared to other grain species, which could modify enzyme activity [6] [9].…”
Section: Resultssupporting
confidence: 80%
“…using a dedicated sets of regents (Biosystems S.A. and Diagnostic Systems GmbH). The SCFA and ammonia concentrations as well as the carbohydrate‐digesting enzyme activity in digesta were determined as described elsewhere (Miltko et al, 2016; Rajtar et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Over 20 rye varieties were assessed for amino acid digestibility in hens, as measured by fecal matter, and the authors found that amino acid digestibility substantially varied (34%–71%) across varieties for lysine, methionine, threonine, and tryptophan (Zuber et al., 2016). Other workers have compared different rye hybrids or OPVs for differences in apparent ileal digestibility in pigs (McGhee & Stein, 2020), and ruminal fermentation in sheep (Rajtar et al., 2021), among other studies. Overall, it is clear that variation exists for important feed quality traits, and such traits could be targeted by rye breeders.…”
Section: Prospects For Breeding Rye For Nutrition Flavor and Qualitymentioning
confidence: 99%